An assessment of genetic variability for drought tolerance in rice - Kushwaha, Brij Kishore; Gobu, R; Lal, Jai Prakash (ORYZA-An International Journal of Rice, 2019)
The genetic variability for yield and yield contributing traits were studied in forty genotypes of rice under moisture-stress (rainfed) and moisture non-stress (irrigated) conditions. The results revealed highly significant differences among the genotypes for all the characters studied. This indicated the ample scope for selection of promising genotypes from the present set of genotypes for yield improvement. The high estimates of GCV and PCV coupled with high heritability and expected genetic advance for yield and important yield contributingtraits showed their importance in selection for improving rice yield. The correlation study revealed that grain yield per plant had strong positive associations with effective panicle bearing tillers, days to 50 % flowering,days to maturity, panicle weight, filled grains per panicle, total grains per panicle and length of main panicle. This indicated that grain yield of rice can be improved under both the environments having higher per se performances for the above traits. The genotypes such as HUR 105, NDR 359, Swarna were found to be best for yield and yield contributing traits. However, based on the different drought parameters, the varieties such as HUR105, HUR 4-3 and IET-20556 has been identified as drought tolerant which might be utilised in futurebreeding programmes.